1992
DOI: 10.1111/j.1365-2427.1992.tb00580.x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of the egg‐ratio method: estimated versus observed death rates

Abstract: 1. The accuracy of death-rate estimates provided by the egg-ratio method was assessed by directly measuring the real death rates of six large laboratory Daphnia populations for 40 days.2. Of six models tested the Kawecki iterative model gave the best relationship to real death rates in terms of variance explained, bias, and fit at both 4-and 8-day sampling intervals. Although considered theoretically correct by persons familiar with the mathematics of egg-ratio models, the Edmondson-Paloheimo model gave slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…With the dynamics as simulated, the population surface method generated markedly more accurate parameter estimates than either cohort analysis or the population projection matrix method and somewhat better estimates than the systems identification technique. Tests of estimation procedures on simulated data remain a powerful means of assessing method accuracy and precision, although comparison with actual mortality measured in enclosures is also possible (Brett et al 1992). Unlike systems identification, the population surface method does not require prior specification of the functional form of birth and death rate variation over time nor does it suffer from the demographic instabilities to which systems identification is prone (Wood and Nisbet 199 1).…”
Section: Discussionmentioning
confidence: 99%
“…With the dynamics as simulated, the population surface method generated markedly more accurate parameter estimates than either cohort analysis or the population projection matrix method and somewhat better estimates than the systems identification technique. Tests of estimation procedures on simulated data remain a powerful means of assessing method accuracy and precision, although comparison with actual mortality measured in enclosures is also possible (Brett et al 1992). Unlike systems identification, the population surface method does not require prior specification of the functional form of birth and death rate variation over time nor does it suffer from the demographic instabilities to which systems identification is prone (Wood and Nisbet 199 1).…”
Section: Discussionmentioning
confidence: 99%
“…Consequences -Overlooking egg mortality can have a serious impact on computing population birth and death rates, resulting in overestimates of both rates. For instance, Brett et al (1992) found that Paloheimo estimates of death rate overestimated observed death rates by 0.015-a bias that might have been caused by the occurrence of NDE. Moreover, the occurrence of NDE will lead to an apparent skewness of the egg-age distribution toward younger stages.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies have focused on the production of different groups of zooplankton and their interactions within the food web, comparatively little is known about the impact of nonconsumptive mortality on zooplankton population dynamics (Andersen 1997). Few articles address zooplankton mortality per se (Clarke and Carter 1974;Prepas and Rigler 1978;Ghilarov 1985;Gabriel et al 1987;Brett et al 1992). There is general agreement that consumptive mortality is the most important factor determining zooplankton population dynamics (Gliwicz and Pijanowska 1989).…”
mentioning
confidence: 99%
“…In culture experiments, mortality rates can be measured relatively easily (Brett et al 1992). Under natural conditions, mortality is usually estimated as the difference between a calculated estimate of birth rate (b) and estimated population growth rate (r) (Clarke and Carter 1974;Prepas and Rigler 1978;Rigler and Downing 1984;Ghilarov 1985).…”
mentioning
confidence: 99%
See 1 more Smart Citation